Key success factors toward MICE industry: A systematic literature review / Muhammad Saufi Anas ... [et al.] - Anas, Muhammad Saufi; Maddiah, Nurul Amirah; Noor Eizamly, Nurin Uzma Eizzaty; Sulaiman, Nadiahtul Aisyah; Wee, Hassnah (Faculti of Hotel and Tourism Management, Universiti Teknologi MARA Cawangan Selangor, 2020)
Meeting, Incentive, Convention, and Exposition (MICE) industry is essential to the country as it directly benefits entrepreneurs in the tourism sector and contributes to improving the local economy. The MICE industry benefits the host city through economic growth, as well as providing greater tourism excellence to the city. However, there is limited literature on the identification of critical success factors that play important roles to the success of MICE event industry. Therefore, it is essential to explore the strategies driven by the industry by conducting a systematic literature review from existing literature and outline key success factors of MICE industry as well as highlighting the similarities of the findings on this topic. The crucial aspects investigated in the research are business travelers’ motivation, perception on MICE industry, motivation attending MICE event, key performance indicator, MICE attendees’ satisfaction, marketing strategies, technological trends, and challenges faced by the industry. Systematic literature was conducted based on recommended procedures by searching multiple databases, data synthesis, and analysis. A total of 39 publications comprising full-text research papers published within ten years (2008-2018) were identified for the review. The findings of this systematic review are useful for empirical studies investigate the sustainability strategies of MICE industry such as driving forces influencing the success of the industry, key performance indicators, and challenges. Journal